2006
DOI: 10.1892/0891-6640(2006)20[569:pvocvo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Clinicopathologic Variables Obtained at Admission and Effect of Antiendotoxin Plasma on Survival in Septic and Critically Ill Foals

Abstract: This prospective study compared survival rates of critically ill and septic foals receiving 1 of 2 different types of commercial equine plasma and analyzed admission variables as possible predictors of survival. Standardized clinical, hematologic, biochemical, and hemostatic admission data were collected and foals received either conventional commercially available hyperimmune equine plasma or equine plasma specifically rich in antiendotoxin antibodies in a double-blinded, coded fashion. Sepsis was defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 16 publications
2
30
1
Order By: Relevance
“…Low erythrocyte count 12-48 h after birth was found to be a risk factor for neonatal foals to develop systemic disease with diarrhoea. Peek et al (2006) observed that a low total RBC count was a statistically significant predictor of overall foal mortality and that this could reflect anaemia, low-grade haemolysis or granulocytic and erythropoetic precursor suppression. Rossdale (1972) reported that a subnormal RBC count and haemoglobin content may be due to a reduced haemopoietic activity caused by bacterial toxins.…”
Section: Discussionmentioning
confidence: 93%
“…Low erythrocyte count 12-48 h after birth was found to be a risk factor for neonatal foals to develop systemic disease with diarrhoea. Peek et al (2006) observed that a low total RBC count was a statistically significant predictor of overall foal mortality and that this could reflect anaemia, low-grade haemolysis or granulocytic and erythropoetic precursor suppression. Rossdale (1972) reported that a subnormal RBC count and haemoglobin content may be due to a reduced haemopoietic activity caused by bacterial toxins.…”
Section: Discussionmentioning
confidence: 93%
“…Despite substantial advances in medical management, sepsis continues to represent a leading cause of illness and death in horses (Hoffman et al 1992;Cohen et al 1994;Werners et al 2005;Peek et al 2006). The body's systemic inflammatory response to microbial invasion can lead to rapid deterioration despite pathogen control, which presents a challenge to equine practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…The issue most often on focus is however, by far, bacterial infection -especially in respiratory diseases [34,[36][37][38][39][40][41] -and such of its short-or long-term sequelae as septic shock with coagulopathy [42][43][44][45], laminitis [46], or osteomyelitis [47].…”
Section: Introductionmentioning
confidence: 99%